Black Soldier Fly (Hermetia illucens L.) Larval Development as Affected by Different Substrates - Sucdad, Septer (Universitas Andalas, 2024)
With the rising demand for sustainable protein sources and effective waste management solutions, Black Soldier Fly (BSF) larvae (Hermetia illucens) have gained attention for their ability to convert organic waste into high-protein biomass. This study investigates the effects of different organic substrates on the growth and nutritional quality of BSF larvae, aiming to identify optimal substrate types for enhancing protein production and supporting sustainable waste management. Conducted in Tomay, La Trinidad, Benguet from January to March 2022, the experiment compared the larval development duration, crude protein content, and associated rearing costs of BSF larvae fed with cabbage trimmings (control), banana peelings, and retrograded rice. The larvae’s development period, from first to sixth instar, ranged from 15 to 17 days under room temperature conditions of 24°C to 30°C and relative humidity levels between 52% and 99%. Results showed that larvae fed on banana peelings achieved the highest crude protein content at 17.81% with a moisture content of 61.11%, followed closely by cabbage trimmings with 17.34% protein and 64.22% moisture, and retrograded rice with 16.82% protein and 63.96% moisture. These differences in protein and moisture content suggest that substrate type significantly influences the nutritional quality of BSF larvae, with implications for their use as a sustainable protein source. In terms of cost, rearing BSF larvae on banana peelings resulted in the highest expenses (PhP3,343.00), followed by cabbage trimmings (PhP3,104.00) and retrograded rice (PhP2,970.00), with total experimental costs amounting to PhP9,509.50. This study highlights that substrate choice affects not only the growth rate and nutrient content of BSF larvae but also the economic feasibility of BSF rearing.